Promoting the Products Offered by “La Lisa Hotel” with an Effective Promotional Video - Yoko Amirudin (Institute of Research and Community Outreach - Petra Christian University, 2019)
Ayola La Lisa is a a 3.5 star hotel which is located at Nginden street no 82. This hotel has 121 rooms, 4 meeting rooms, a pool, a restaurant, a coffee shop, and etc. Moreover, this hotel has more spacious rooms than its rivals and one meeting room that can accommodate up to 200 people. The main problem that La Lisa currenly facing is the potential customers did not give positive feedback while the sales team offered the products. Most importantly, this promotional tool failed to project La Lisa uniqueness. Because of this problem, La lisa could not get the attention from as potential customers mostly from all over Surabaya such as government officers. Therefore, the solution of the problem is to make a promotional video. With this video, the potential customers will be more interested when they see motion pictures highlighting the unique selling points, rarther than just a brochure. The unique selling points that will be highlighthed is to focus on the private meeting room and its other supporting facilities such as the lunch, the rooms, and the ambience. By having this video, the sales and marketing team will be easier to promote the hotel more effectively to its potential customers. Keywords: promotion, branding, unique selling point (USP), promotional video